Informed Speculation and Hedging in a Noncompetitive Securities Market - Spiegel, Matthew; Subrahmanyam, Avanidhar (Review of Financial Studies, 1992)
[We examine an adverse selection model of trading in which both informed and uninformed traders are rational, maximizing agents. Replacing the price inelastic "noise" or "liquidity" traders with strategic, utility-maximizing hedgers permits an explicit analysis of the uninformed traders' welfare, and demonstrates that several comparative statics obtained from the standard paradigm of Kyle (1984, 1985) are altered significantly upon endogenizing the trading motives of these agents. In contrast to extant models, market liquidity and price efficiency are both nonmonotonic in the number of uninformed hedgers in the market. Also, the welfare of hedgers monotonically decreases with the number of informed traders, despite greater competition between the informed.]